Distinct VSV-based Nipah virus vaccines expressing either glycoprotein G or fusion protein F provide homologous and heterologous protection in a nonhuman primate modelResearch in context - Emmie de Wit; Friederike Feldmann; Jacqueline Cronin; Kerry Goldin; Reinaldo Mercado-Hernandez; Brandi N. Williamson; Kimberly Meade-White; Atsushi Okumura; Julie Callison; Sarah Weatherman; Rebecca Rosenke; Victoria A. Avanzato; et al. (EBioMedicine, 2023)
Summary: Background: Nipah virus (NiV) causes recurrent outbreaks of lethal respiratory and neurological disease in Southeast Asia. The World Health Organization considers the development of an effective vaccine against NiV a priority. Methods: We produced two NiV vaccine candidates using the licensed VSV-EBOV vaccine as a backbone and tested its efficacy against lethal homologous and heterologous NiV challenge with Nipah virus Bangladesh and Nipah virus Malaysia, respectively, in the African green monkey model. Findings: The VSV-EBOV vaccine expressing NiV glycoprotein G (VSV-NiVG) induced high neutralising antibody titers and afforded complete protection from homologous and heterologous challenge. The VSV-EBOV vaccine expressing NiV fusion protein F (VSV-NiVF) induced a lower humoral response and afforded complete homologous protection, but only partial heterologous protection. Both vaccines reduced virus shedding from the upper respiratory tract, and virus replication in the lungs and central nervous system. None of the protected animals vaccinated with VSV-NiVG or VSV-NiVF showed histological lesions in the CNS, but one VSV-NiVF-vaccinated animal that was not protected developed severe meningoencephalitis. Interpretation: The VSV-NiVG vaccine offers broad protection against NiV disease. Funding: This study was supported by the Intramural Research Program, NIAID, NIH.